Nanocomposites as biomolecules delivery agents in nanomedicine - Bamburowicz-Klimkowska, Magdalena (J Nanobiotechnology, 2019)
Nanoparticles (NPs) are atomic clusters of crystalline or amorphous structure that possess unique physical and chemical properties associated with a size range of between 1 and 100 nm. Their nano-sized dimensions, which are in the same range as those of vital biomolecules, such as antibodies, membrane receptors, nucleic acids, and proteins, allow them to interact with different structures within living organisms. Because of these features, numerous nanoparticles are used in medicine as delivery agents for biomolecules. However, off-target drug delivery can cause serious side effects to normal tissues and organs. Considering this issue, it is essential to develop bioengineering strategies to significantly reduce systemic toxicity and improve therapeutic effect. In contrast to passive delivery, nanosystems enable to obtain enhanced therapeutic efficacy, decrease the possibility of drug resistance, and reduce side effects of “conventional” therapy in cancers. The present review provides an overview of the most recent (mostly last 3 years) achievements related to different biomolecules used to enable targeting capabilities of highly diverse nanoparticles. These include monoclonal antibodies, receptor-specific peptides or proteins, deoxyribonucleic acids, ribonucleic acids, [DNA/RNA] aptamers, and small molecules such as folates, and even vitamins or carbohydrates.